Effect of dry cord care versus chlorhexidine cord care on cord separation time in healthy newborns: A comparative study (Journal of Kathmandu Medical College, 2020)
Background:  Umbilical cord infection (omphalitis) is a major cause of neonatal mortality and morbidity in a developing country like Nepal. Detached umbilical stump is an important colonizing site for different types of bacteria and it also provides direct access to bloodstream. Hence, inadequate cord care may lead to omphalitis as well as neonatal sepsis.Objectives: This study aims to compare two different cord care regimens (dry cord care versus chlorhexidine cord care) on their cord separation time and the incidence of omphalitis.Methodology: This is a comparative observational study conducted at the Neonatal unit of Kathmandu Medical College over a three months period (August 2019 to October 2019).  All newborn babies born between 37 to 42 weeks of gestation were enrolled. Randomization for dry cord care and chlorhexidine cord care group was done via computer generated numbers. Statistical package for social sciences 19 version was used for statistical analysis. Results: Among 514 term babies, 256 babies were included in the dry cord care group while 258 babies were enrolled in the chlorhexidine cord care group. The two groups had similar baseline characteristics. The mean cord separation time in the dry cord care group was 7.70±1.2 days (range 3-15 days), whereas in the chlorhexidine group, it was 7.77±1.4 days (range 4-18 days). Conclusion: There was no significant difference between the cord separation times in dry and chlorhexidine cord care regimens. Both dry cord care and chlorhexidine cord care regimens were found to be safe and effective.